The Significance of Reporting and Recognition of CSR Expenses: A Study of PT Alamtri Resources Indonesia Tbk - Siti Nura'azizah Tompunu; Ainun Arizah; Indriana Indriana (MUQADDIMAH: Jurnal Ekonomi, Manajemen, Akuntansi dan Bisnis, 2026)
Corporate Social Responsibility (CSR) has become an essential component of corporate sustainability, particularly in industries with significant social and environmental impacts. Despite the growing practice of CSR reporting, information regarding the recognition and disclosure of CSR expenditures often remains limited and predominantly narrative in nature. An interpretive qualitative approach was employed to examine the meaning embedded in the disclosure and recognition of CSR expenditures within the reporting practices of PT Alamtri Resources Indonesia Tbk. The study utilized document analysis of annual reports and sustainability reports published during the 2022–2024 period. The analysis focused on the presentation of CSR information, the recognition of CSR expenditures, and the broader significance attached to these practices. The findings indicate that CSR activities are disclosed systematically through annual reports, sustainability reports, and digital communication platforms, covering programs in education, economy, health, socio-cultural development, and environmental sustainability. CSR expenditures are presented not merely as operational costs but as social investments intended to generate long-term benefits for both the company and society. The reporting practices also function as instruments for strengthening stakeholder relationships, maintaining organizational legitimacy, and demonstrating corporate accountability. These findings contribute to the understanding of CSR reporting by highlighting the strategic and symbolic dimensions of CSR expenditure recognition beyond its accounting function, particularly within the context of Indonesia’s mining industry.